2019
DOI: 10.1002/epi4.12327
|View full text |Cite
|
Sign up to set email alerts
|

The utility of an automated and ambulatory device for detecting and differentiating epileptic and psychogenic non‐epileptic seizures

Abstract: Objective Accurate differentiation between epileptic seizures (ES) and psychogenic non‐epileptic seizures (PNES) can be challenging based on history alone. Inpatient video EEG monitoring (VEM) is often needed for a definitive diagnosis. However, VEM is highly resource intensive, is of limited availability, and cannot be undertaken over long periods. Previous research has shown that time‐frequency analysis of accelerometer data could be utilized to differentiate between ES and PNES. Using a seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…While this analysis focuses specifically on delay to VEM in patients with dissociative seizures, prior to VEM, the certainty of the diagnosis of dissociative seizures was lower. Since these levels of diagnostic certainty were established, other methods have been used to risk-stratify or diagnose patients with dissociative seizures prior to inpatient VEM including, but not limited to ambulatory video-EEG, wearable activity monitors, patient-provided videos, and clinical screening scores [28,[73][74][75][76][77][78]. While none of these have been shown to be equivalent in safety and efficacy to inpatient VEM yet, they may provide alternatives when inpatient VEM is not available.…”
Section: Discussionmentioning
confidence: 99%
“…While this analysis focuses specifically on delay to VEM in patients with dissociative seizures, prior to VEM, the certainty of the diagnosis of dissociative seizures was lower. Since these levels of diagnostic certainty were established, other methods have been used to risk-stratify or diagnose patients with dissociative seizures prior to inpatient VEM including, but not limited to ambulatory video-EEG, wearable activity monitors, patient-provided videos, and clinical screening scores [28,[73][74][75][76][77][78]. While none of these have been shown to be equivalent in safety and efficacy to inpatient VEM yet, they may provide alternatives when inpatient VEM is not available.…”
Section: Discussionmentioning
confidence: 99%
“…17 Algorithms specific for GTCSs have been reported, accurately differentiating between GTCSs and convulsive psychogenic nonepileptic seizures. 18,19 However, a significant number of false alarms occur with these devices (0.2-0.7/d). 2 Therefore, the specificity of the detections needs further confirmation for accurate quantification of the GTCS burden.…”
Section: Characterization Of Seizure T Ype and Frequencymentioning
confidence: 99%
“…Phase 3 and 4 clinical validation studies showed that wearable devices detect GTCSs with a high sensitivity (90%‐96%), based on accelerometry, 14,15 surface electromyography, 16 or multimodal biosignals 17 . Algorithms specific for GTCSs have been reported, accurately differentiating between GTCSs and convulsive psychogenic nonepileptic seizures 18,19 . However, a significant number of false alarms occur with these devices (0.2‐0.7/d) 2 .…”
Section: Automated Characterization Of Seizure Type and Frequencymentioning
confidence: 99%
“…Some authors tried to correlate PNES with neurophysiological data. Naganur et al (2019) showed that the evolutionary pattern of the frequencies of rhythmic movement artifacts on EEG during PNES differs from that of ES. Convulsive PNES were demonstrated to display a characteristic pattern of rhythmic movement artifact that remains stable over time during the event, whereas the EEG activity during convulsive ES tends to evolve throughout.…”
Section: Pnes: a Diagnostic Challengementioning
confidence: 99%